Criminal Penalties For Corruption In Decision No. 46/Pid.Sus-Tpk/2022 / Pn In The Perspective Of Islamic Law - Asliani, Asliani (Faculty of Law, Universitas Pekalongan, 2024)
The purpose of this research is to find out how the view Islam against corruption and the application of fines according to Islamic Criminal Law. Research methods used in this study are normative juridical research and can concluded: Corruption in Islam is acts of transgression. Islamic Law aims to create for the benefit of mankind with what is referred to as maqashidussy Shariah. Context perspective of Islamic teachings more broadly, the practice of corruption is actions contrary to the principle justice, accountability, and responsibility answer. Corruption and all its consequences the negative causes various distortions to the life of the country and people who can be categorized into in acts of corruption on Earth which is the Curse of Allah swt and Regulation Of Islamic Criminal Law putting corruption in the category jarimah takzir, takzir is a sanction the law applied to a person who has a finger or thumb criminal offense violations relating to human rights God and Man, and these violations are not strictly defined form of sanction in the Quran and Hadith because it is not determined explicitly then to be a competent judge or local authorities. Legal sanctions takzir can be a fine which is one type of alternative punishment should be promoted as the most civilized form of punishment Islam was introduced fourteen centuries ago.